Whispers in the dark eaudiobook Kgi series, book 4. - Banks, Maya (KGI, 2012)
New York Times and USA Today bestselling author Maya Banks here continues her enthralling series based around the Kelly brothers-six rugged men who make up an elite military group. When Nathan Kelly is finally rescued from behind enemy lines, he credits his life to Shea, whose psychic voice sustained his spirit through it all. But now Shea has gone silent, and Nathan fears she's in trouble. Can he find Shea in time to repay the tremendous debt he owes her?